Synthesis, Characterization, Viscosity and Thermo Analytical Studies of Schiff Base Polymers Derived from 6,6-Methylene bis(1-napthaldehyde) - Mughal, M.A.; Mughal, A.; Zuhra Memon, G.; Khuhawar, M.Y.; Qureshi, Sumera (Asian Journal of Chemistry, 2013)
Four new Schiff based polymers were synthesized from 6,6-methylene bis(1-napthaldehyde) through polycondensation of 6,6-methylene bis(1-napthaldehyde) with diamines 1,3-propylenediamine, 1,2- propylenediamine, ethylenediamine and urea in 1:1molar ratio. The monomer 6,6-methylene bis(1-napthaldehyde) was prepared by treating 6,6-methylene bis(1-napthaldehyde) with 1,3,5-trioxane in presence of H2SO4 and CH3COOH, respectively. The polymers poly[6,6-methylenebis(1-napthaldehyde)1,2-propylenediimine] (PMBNPn), poly[6,6-methylenebis(1-napthaldehyde) 1,3-propylenediimine] (PMBNPR), poly[6,6- methylenebis(1-napthaldehyde)ethylenediimine] (PMBNen) and poly[6,6-methylenebis(1- napthaldehyde)urea (PMBNU), were soluble in few organic solvents. The structure of Schiff bases was confirmed by CHN, FTIR, UV-visible spectroscopy, TGA/DTA and viscosity measurements. The polymers showed shift in band position as compared to monomer, due to conversion of carbonyl to azomethine group and the increased values of reduced and intrinsic viscosities than the corresponding monomer attributed to the formation of polymers.